A porous form Coomassie brilliant blue G250-isorhamnetin fluorescent composite coated with acrylic resin for tumor cell imaging - Hu, Jiangpeng; Teng, Bo; Xu, Zhipeng; Wan, Yuanye; Jin, Guofan (Frontiers in Chemistry, 2023)
Four distinct fluorescence complexes, the fluorescent complex-1 (FC-1), fluorescent complex-2 (FC-2), fluorescent complex third (FC-3) and fluorescent complex fourth (FC-4), were created using isorhamnetin and Coomassie brilliant blue G250 as raw materials. The issue of isorhamnetin’s low solubility has been resolved, and isorhamnetin-coomassie brilliant blue G250 now has better biocompatibility. Four different forms of fluorescence compounds’ ultraviolet absorption spectra were identified. It was discovered that FC-2, FC-3, and FC-4, respectively, had double peaks at 483–620 nm. FC-4 had the highest ultraviolet absorption intensity, whereas FC-1 exhibited the most consistent and longest wavelength of ultraviolet absorption. Transmission electron microscopy revealed that the acrylic resin evenly disseminated the Coomassie brilliant blue G250-isorhamnetin complex in an amorphous flocculent form. Human prostate cancer cells (PC3) and human cervical cancer cells (HeLa) were investigated in the (Cell Counting Kit-8) CCK8 experiment under 10 different concentration circumstances, and the proliferation impact was 64.30% and 68.06%, respectively. Shown the complex’s strong anti-tumor properties and minimal cytotoxicity. Through in vitro imaging of tumor cells, it was found that FC-1’s fluorescent complex has high selectivity and can accurately infiltrate tumor cells, proving that it is biocompatible. The design not only addresses the issue of isorhamnein-Coomassie Bright Blue G250’s bioavailability, but it also has an effective visual fluorescence targeting effect.